Strategies for assessing and preventing cardiovascular disease risk in inflammatory bowel disease patients: A meta-analysis and meta-regression and bibliometric review. - Lu-Fei Liu; Yi-Wei Fan; Ye Lv; Zhao-Xia Liu; Xiao-Ce Dai (PLoS ONE, 2025)
Objective To evaluate how inflammatory bowel disease in adults increases the risk of developing cardiovascular disease. Design Meta-analysis, meta-regression and bibliometric review. Data sources PubMed and Embase were searched from their inception until December 19, 2024. Additionally, a manual search was conducted to identify cohort studies and related systematic reviews. Web of Science Core Collection (WoSCC) database was used to bibliometric analysis. Eligibility criteria Cohort studies assessing the risk of cardiovascular disease (CVD) in adults with inflammatory bowel disease (IBD) were included. Non inflammatory bowel disease exposure was considered as the control group. The risk of bias and the certainty of the evidence were evaluated. Meta analysis, meta regression, sensitivity analysis, and bibliometric analysis of keywords were performed. Results 23 studies, comprising 20 different samples (n=45,887,104), were included. meta-analyses showed adults with IBD regardless of Crohn's disease and ulcerative colitis increased the CVD risk. This risk increased in IBD patients after conducting sensitivity analyses. However, the strength of evidence was deemed very low for all outcomes with substantial heterogeneity observed across all outcomes. The bibliometric review showed the neutrophil-to-lymphocyte ratio can act as a biomarker for predicting IBD severity. Conclusion While inflammatory bowel disease (IBD) may elevate the risk of cardiovascular disease (CVD), current evidence does not support the use of medication for primary prevention. Randomized controlled trials are needed to address this gap in knowledge.